2012
DOI: 10.1100/2012/859243
|View full text |Cite
|
Sign up to set email alerts
|

Nemesia Root Hair Response to Paper Pulp Substrate for Micropropagation

Abstract: Agar substrates for in vitro culture are well adapted to plant micropropagation, but not to plant rooting and acclimatization. Conversely, paper-pulp-based substrates appear as potentially well adapted for in vitro culture and functional root production. To reinforce this hypothesis, this study compares in vitro development of nemesia on several substrates. Strong differences between nemesia roots growing in agar or in paper-pulp substrates were evidenced through scanning electron microscopy. Roots developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
2
0
2
Order By: Relevance
“…Moreover, kinetin could be also tested on N. triphylla shoot propagation as 1 mg.dm -3 of this cytokinin in the culture medium increased the shoot number of Withania somnifera (Sabir et al 2008). As previously developed for other species (Labrousse et al 2012), in vitro rooting and acclimation assays are currently in progress to establish a complete in vitro to ex vitro regeneration protocol for this species. It should be noted that, as in the case of Swertia chirayita described by Joshi and Dhawan (2007), it would be useful to assess the genetic fidelity of micropropagated plants to limit the impact of somaclonal variation on this endangered species.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, kinetin could be also tested on N. triphylla shoot propagation as 1 mg.dm -3 of this cytokinin in the culture medium increased the shoot number of Withania somnifera (Sabir et al 2008). As previously developed for other species (Labrousse et al 2012), in vitro rooting and acclimation assays are currently in progress to establish a complete in vitro to ex vitro regeneration protocol for this species. It should be noted that, as in the case of Swertia chirayita described by Joshi and Dhawan (2007), it would be useful to assess the genetic fidelity of micropropagated plants to limit the impact of somaclonal variation on this endangered species.…”
Section: Resultsmentioning
confidence: 99%
“…plantlets were potted on peat moss alone or in combination with sand at (1:1 v: v), the stems of the in vitro acclimatized plants were allowed to grow up to the highest value [33]. Also, Labrousse et al [34] reported that the use of peat moss as a substrate in vitro culture enhanced rooting and increased the number and length of roots. for the antioxidant potential in B. pauciflora.…”
Section: Acclimatizationmentioning
confidence: 99%
“…It is known that in in vitro conditions, the propagules are cultured in test tubes or vessels under aseptic conditions, low light irradiance and high relative humidity [75]. Besides, the culture medium contains nutrients and sugar, and thus the propagules are usually grown heterotrophically since any roots formed are not always functional due to absence of root hairs [74,76]. The results of this study showed that the adaptation of young plantlets to the new environment should be carried out gradually and carefully.…”
Section: Rooting Of Shoots and Acclimatization Of Plantletsmentioning
confidence: 99%